2016
DOI: 10.7717/peerj.2386
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology ofSalmonellasp. in California cull dairy cattle: prevalence of fecal shedding and diagnostic accuracy of pooled enriched broth culture of fecal samples

Abstract: BackgroundThe primary objective of this cross-sectional study was to estimate the crude, seasonal and cull-reason stratified prevalence of Salmonella fecal shedding in cull dairy cattle on seven California dairies. A secondary objective was to estimate and compare the relative sensitivity (Se) and specificity (Sp) for pools of 5 and 10 enriched broth cultures of fecal samples for Salmonella sp. detection.MethodsSeven dairy farms located in the San Joaquin Valley of California were identified and enrolled in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
0
14
2
Order By: Relevance
“…Salmonella was cultured from approximately 30% of the sampled culled adult dairy cows at the abattoir in Wuhan, China. The prevalence recorded from this study was slightly higher than that reported in other studies from the USA (25%; 3%) and Italy (0%) in culled dairy cows [ 22 , 23 , 24 ]. In China, a prevalence of approximately 20% was reported in cattle sampled at multiple abattoirs and it was postulated that the feces and the hides posed a high risk for contamination with Salmonella [ 13 ].…”
Section: Discussioncontrasting
confidence: 78%
“…Salmonella was cultured from approximately 30% of the sampled culled adult dairy cows at the abattoir in Wuhan, China. The prevalence recorded from this study was slightly higher than that reported in other studies from the USA (25%; 3%) and Italy (0%) in culled dairy cows [ 22 , 23 , 24 ]. In China, a prevalence of approximately 20% was reported in cattle sampled at multiple abattoirs and it was postulated that the feces and the hides posed a high risk for contamination with Salmonella [ 13 ].…”
Section: Discussioncontrasting
confidence: 78%
“…This decrease in sensitivity is of lesser magnitude when testing using PCR-CUL compared to CUL alone (90% vs. 74%). The estimated mean relative sensitivity of CUL for FP and BP in this study are slightly higher and had less variability as compared to the estimates reported in the study of Abu Aboud et al (2016) which may be explained by differences over time despite being the same herds. However, these studies produced comparable estimates (mean and 95% CI) for relative specificity of CUL method.…”
Section: Discussioncontrasting
confidence: 74%
“…Abu Aboud et al (2016) reported fecal Salmonella prevalence ranging from 1.97% to 7.11% from a study of 249 cull cows sampled on 7 California dairies, 6 of which were the same herds in the current study. In comparison, the same herds in our study had a Salmonella prevalence of 21% to 35% across seasons.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition to the role fecal microbes play in the nitrogen cycle, dairy cattle are reservoirs for zoonotic bacterial pathogens such as Escherichia coli O157:H7, Salmonella spp. (Abu Aboud et al, 2016) and Campylobacter jejuni (USDA, 2011). Both E. coli and Salmonella can survive in soil when introduced via application of slurry – a mixture of urine and feces – or manure to crops (Semenov et al, 2009).…”
Section: Introductionmentioning
confidence: 99%